The Detection of Communicative Signals Directed at the Self in Infant Prefrontal Cortex - Grossmann, Tobias; Parise, Eugenio; Friederici, Angela (Frontiers in Human Neuroscience, 2010)
A precondition for successful communication between people is the detection of signals indicating the intention to communicate, such as eye contact or calling a person’s name. In adults, establishing communication by eye contact or calling a person’s name results in overlapping activity in right prefrontal cortex, suggesting that, regardless of modality, the intention to communicate is detected by the same brain region. We measured prefrontal cortex responses in 5-month-olds using near-infrared spectroscopy (NIRS) to examine the neural basis of detecting communicative signals across modalities in early development. Infants watched human faces that either signaled eye contact or directed their gaze away from the infant, and they also listened to voices that addressed them with their own name or another name. The results revealed that infants recruit adjacent but non-overlapping regions in the left dorsal prefrontal cortex when they process eye contact and own name. Moreover, infants that responded sensitively to eye contact in the one prefrontal region were also more likely to respond sensitively to their own name in the adjacent prefrontal region as revealed in a correlation analysis, suggesting that responding to communicative signals in these two regions might be functionally related. These NIRS results suggest that infants selectively process and attend to communicative signals directed at them. However, unlike adults, infants do not seem to recruit a common prefrontal region when processing communicative signals of different modalities. The implications of these findings for our understanding of infants’ developing communicative abilities are discussed.